In vitro comparison of biofilm formation and acidogenicity between human breast milk and other milk formulas. Issue 2 (August 2020) - Trongsilsat, Sanpob; Lapirattanakul, Jinthana; Surarit, Rudee; Smutkeeree, Apiwan
Abstract: Objective: To evaluate the ability and acidogenicity of human breast milk (HBM) biofilm formation relative to other milk formulas. Materials and methods: Pooled HBM from six donor mothers, plain milk-based formula, milk-based formula supplemented with sucrose, soy-based formula, and brain heart infusion (BHI) containing 10% sucrose were utilized for the evaluation of biofilm formation and its acidogenicity. Biofilms formed by these tested groups, with and without 10 5 CFU/ml of Streptococcus mutans, were stained with crystal violet that was quantified by measuring the absorbance value (OD) at 595 nm. The acidogenicity of the biofilms was assessed after a 24-hour incubation period. Statistical analysis: Multivariate analysis, the Kruskal Wallis test, and the Bonferroni test were performed. A P-value less than 0.05 was considered to be statistically significant. Results: HBM containing S. mutans had significantly less potential to form biofilms as compared to other milk formulas. The overall biofilm OD value was significantly lower in the HBM group as compared to the other groups (P < 0.05). Additionally, the pH of HBM biofilm formation did not drop under critical pH after 24 h of incubation. Conclusions: HBM tends to be non-cariogenic due to its low acidogenicity and limited biofilm formation.